Functional outcomes of open laminectomy, minimally invasive, and endoscopic biportal decompression surgery in lumbar stenosis: systematic review and meta-analysis - Aziz, Mukhlis; Widhiyanto, Lukas; Lestari, Pudji (Edelweiss Applied Science and Technology, 2024)
Lumbar spinal stenosis (LSS) is a common degenerative condition that often requires decompression surgery. Various techniques, including open laminectomy, minimally invasive unilateral laminotomy bilateral decompression (MIS-ULBD), and unilateral biportal endoscopic (UBE) surgery, are utilized. This study compares the functional outcomes and complications of these methods. A systematic review and meta-analysis were conducted, analyzing studies from PubMed, Springerlink, and other databases. The key variables studied included the Visual Analog Scale (VAS) for pain, Oswestry Disability Index (ODI), intraoperative blood loss, hospital stay duration, operative time, and postoperative complications. A total of 14 studies with 1,427 patients aged 52.35-74.52 years were included. MIS resulted in shorter operative times compared to UBE, but UBE had a lower complication rate. UBE also demonstrated superior outcomes in terms of VAS pain reduction, ODI scores, and shorter hospital stays compared to both MIS and open laminectomy. UBE and MIS each present post-operative advantages. UBE offers faster recovery and reduced pain, while MIS has the benefit of shorter surgery times. Despite the steep learning curve and more complex instrumentation required, UBE is a safe and effective alternative to traditional decompression techniques, offering better functional outcomes in LSS patients compared to MIS and open laminectomy.